Raízes intelectuais da democracia brasileira: linguagens políticas e a formação da república - Marcelo Sevaybricker Moreira (2013)
This work investigates the way in which the intellectual traditions of Brazil, particularly those that seek to define the paths consolidation of Brazilian democracy, is rooted in practice and political culture. Therefore, the work turns to the works of some Brazilian intellectuals who, according to the adopted hypothesis, formulated political languages fundamental to think contemporary Brazilian democracy. They are: Raymundo Faoro, Celso Furtado, Wanderley Guilherme dos Santos and Fernando Henrique Cardoso. The analysis of the work of each of these authors, who shared the same historical context, reveals that democracy was designed according to a field of concepts and values different. In addition, we sought to evaluate critically the political languages of these authors in the light of two major traditions of Political Theory, namely, republicanism and liberalism. These traditions, revisited recently by the debate about freedom, serve as a theoretical framework for assessing the contribution of each of the Brazilian intellectuals, as well as for the analysis of the formation of national democracy, its advances and limitations. The research highlights the shortcomings of the conceptual and normative liberal tradition to think the main dilemmas of democracy in general, and especially of Brazilian democracy. Also defends the wealth and the need to incorporate more systematic centrality and intellectual traditions of the country for the studies produced by mainstream Political Science, adopting thus a perspective historicist and attentive to mediations between political theory and practice.